A Case of Uncomplicated Bacteremia Caused by Capnocytophaga canimorsus in an Immunocompetent Patient - Taniyama, Daisuke; Imoto, Kazuya; Suzuki, Michio; Imaoka, Koichi (Curēus (Palo Alto, CA), 2023)
This report describes uncomplicated bacteremia caused by Capnocytophaga canimorsus in an immunocompetent woman who presented with rigor and fever. She was hemodynamically stable. Two blood samples were immediately cultured because rigor indicated bacteremia. Although her symptoms were relieved, Gram-negative rods grew from blood cultures. She noted that she had been bitten by her dog before the first examination. The bacterium was confirmed as C. canimorsus by gene analysis. Infection with C. canimorsus can be fatal when accompanied by sepsis in elderly or immunocompromised patients. However, this case was considered rare as the patient was 41 years old and immunocompetent.